Sharing One Biographical Detail Elicits Priming between Famous Names: Empirical and Computational Approaches - Ihrke, Matthias; Brennen, Tim (Frontiers in Psychology, 2011)
In this paper three experiments and corresponding model simulations are reported that investigate the priming of famous name recognition in order to explore the structure of the part of the semantic system dealing with people. Consistent with empirical findings, novel computational simulations using Burton et al.'s interactive activation and competition model point to a conceptual distinction between how priming is initiated in single- and double-familiarity tasks, indicating that priming should be weaker or non-existent for the single-familiarity task. Experiment One demonstrates that, within a double-familiarity framework using famous names, categorial and associative priming are reliable effects. Pushing the model to the limit, it predicts that pairs of celebrities who are neither associatively- nor categorially-related but who share single biographical features, both died in a car crash for example, should prime each other. Experiment Two investigated this in a double familiarity task but the effect was not observed. We therefore simulated and realized a pairwise learning task that was conceptually similar to the double-familiarity decision task but allowed to strengthen the underlying connections. Priming based on a single biographical feature could be found both in simulations and the experiment. The effect was not due to visual or name similarity which were controlled for and participants did not report using the biographical links between the people to learn the pairs. The results are interpreted to lend further support to structural models of the memory for persons. Furthermore, the results are consistent with the idea that episodic features known about people are stored in semantic memory and are automatically activated when encountering that person.